SANKSI YANG DITERIMA OLEH PEJABAT PEMBUAT AKTE TANAH DALAM PEMBUATAN AKTA AUTENTIK YANG CACAT HUKUM (STUDI PUTUSAN: PN JAKSEL NO. 124/PDT.G/2017/PN.JKT.SEL) - Andi Pratono; Tjempaka Tjempaka (Jurnal Hukum Adigama, 2019)
Indonesia is the law of state or law state, as a law state country, Indonesia must have 3(three) important element such as legal certainty, justice, and expediency. Those main elements represent all the law state. In community, people everyday acts always relate to legal act, such as contract, buying or selling object that promised. To ensure those legal act have the ability perfect proof power, those legal act poured in the form of deed. In buying and selling land, a deed of sale and purchase must be made in front authorized official like land deed officer. However land deed officer as public official do make mistake on duty, with the result that party at a disadvantage. Party that loss because of mistake land deed officer, do ask for responsibility by suing the land deed officer to compensate the losses. Land deed officer in carrying out their duties must apply the precautionary principle so as to minimize any mistakes in making the deed. Author is using normative legal research methods, supported by a data which is theory and interviews some expert in land deed officer and Code of Ethics. The legal consequences to the land deed officer due the legal acts are against the law, which is a sanction will be given. The sanction will divided in three types such as sanction according to the Civil Law, Criminal Law and Code of Ethics or Government Regulation about land deed officer.